1996
DOI: 10.1209/epl/i1996-00515-8
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency atomic motion in a model glass

Abstract: A molecular-dynamics simulation is presented which explores the microscopic dynamics of a monatomic model glass. The investigated systems consist of up to 32000 atoms interacting via a Lennard-Jones potential. The normal-modes analysis has been used to determine the pattern of atomic displacements. Except for the highest frequencies, all the vibrational modes are found to be delocalized. In the lowest-frequency region the pattern of atomic displacements associated with a given eigenmode is composed by an uncor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
114
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 17 publications
9
114
1
Order By: Relevance
“…The time scales predicted by the structure factors are in good agreement with those predicted by NMD at low frequencies. Similar agreement has been reported in other models of amorphous materials [6,[76][77][78]. The agreement between the NMD-predicted lifetimes and the structure factor time scales for a-Si at low frequencies indicates (5) and (20) with the DOS sound speed from Table I] that these modes are plane-wave-like and that the wave packets formed by these modes are propagating [4,6].…”
Section: Lifetimessupporting
confidence: 87%
“…The time scales predicted by the structure factors are in good agreement with those predicted by NMD at low frequencies. Similar agreement has been reported in other models of amorphous materials [6,[76][77][78]. The agreement between the NMD-predicted lifetimes and the structure factor time scales for a-Si at low frequencies indicates (5) and (20) with the DOS sound speed from Table I] that these modes are plane-wave-like and that the wave packets formed by these modes are propagating [4,6].…”
Section: Lifetimessupporting
confidence: 87%
“…Recently, it was shown that the spatial distribution of low-frequency quasi-localized normal modes is strongly correlated with the spatial distribution of irreversible reorganization (8). This study and related work (9)(10)(11)(12)(13) underline the importance of understanding the relation between local soft modes and structure in disordered solids. Understanding how features of an inherent structure determine the spatial pattern of motions is of central importance in developing a useful microscopic treatment of glass transitions and is the goal of this article.…”
supporting
confidence: 52%
“…In this case one uses a framework (dynamical matrix, etc.) formally similar to the one customarily adopted for harmonic crystals; however, owing to the lack of translational symmetry of the system, it turns out [22] that the eigenstates cannot anymore be represented by plane waves (PW) even at relatively small wavevectors [26]. A scattering experiment, where Q is fixed, is equivalent -via the fluctuation-dissipation relation-to a response experiment, where one study the time evolution of the system after a sinusoidal perturbation (with period 2π/Q) is applied to the system itself.…”
Section: Discussionmentioning
confidence: 99%